Inflation Targeting and Monetary Policy Transmission Mechanisms in Emerging Market Economies - Mukherjee, Sanchita (IMF Working Papers; Working Paper, 2011)
In this paper we empirically examine the operation of the traditional Keynesian interest rate channel of the monetary policy transmission mechanism in five potential inflation targeting economies in the MENA region and compare it with fourteen inflation targeting (IT) emerging market economies (EMEs) using panel data analysis. Contrary to some existing studies, our empirical results suggest that private consumption and investment in both groups of countries are sensitive to movements in real interest rates. Moreover, we find that the adoption of IT did not significantly alter the operation of the interest rate channel in IT EMEs. Also, the interest rate elasticities of private consumption and private investment vary with the level of development of the domestic financial market. Finally, capital account liberalization have opposite effects on private consumption and private investment in the two groups of countries.